INVESTIGATION OF THE POSSIBILITY AND EFFICIENCY OF RECYCLING OF RECYCLED RECYCLED CONCRETE AND REINFORCED CONCRETE STRUCTURES IN THE CONSTRUCTION OF REINFORCED CONCRETE BRIDGES (American Journal of Research in Humanities and Social Sciences, 2023)
Concrete waste as crushed concrete aggregates (CCA) in structural concrete gives a new purpose and prolongs the technical life of the reference concrete accomplishing closed loop recycling. This research investigates CCA as aggregate replacement in an industrial reference concrete recipe as fine aggregate fractions and overall aggregate replacement. Experimental study of CCA concrete is conducted by testing compressive strength and workability. Results show that CCA concrete has inferior compressive strength and workability than reference concrete due to the adhered mortar and flakiness index of CCA, properties which differentiate CCA from reference concrete aggregates. These properties influence the aggregate packing density and water absorption properties of CCA, crucial to concrete workability and compressive strength.